2021
DOI: 10.3390/polysaccharides2020029
|View full text |Cite
|
Sign up to set email alerts
|

Oxi-HA/ADH Hydrogels: A Novel Approach in Tissue Engineering and Regenerative Medicine

Abstract: Hyaluronic acid (HA) is a natural polyelectrolyte abundant in mammalian connective tissues, such as cartilage and skin. Both endogenous and exogenous HA produced by fermentation have similar physicochemical, rheological, and biological properties, leading to medical and dermo-cosmetic products. Chemical modifications such as cross-linking or conjugation in target groups of the HA molecule improve its properties and in vivo stability, expanding its applications. Currently, HA-based scaffolds and matrices are of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 138 publications
3
2
0
Order By: Relevance
“…A wide range of Young's moduli have been observed with hydrazone-crosslinked HA hydrogels with values ranging between 1–2000 Pa reported in the literature. 36 In comparison, our HA hydrogels exhibited relatively low compressive moduli within a narrow range of 4.5–42.2 Pa. Others have found that a higher degree of modification for HA-ADH led to stiffer hydrogels, which was similar to what we observed for the 40 kDa hydrogels. 35 …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…A wide range of Young's moduli have been observed with hydrazone-crosslinked HA hydrogels with values ranging between 1–2000 Pa reported in the literature. 36 In comparison, our HA hydrogels exhibited relatively low compressive moduli within a narrow range of 4.5–42.2 Pa. Others have found that a higher degree of modification for HA-ADH led to stiffer hydrogels, which was similar to what we observed for the 40 kDa hydrogels. 35 …”
Section: Resultssupporting
confidence: 85%
“…A wide range of Young's moduli have been observed with hydrazone-crosslinked HA hydrogels with values ranging between 1-2000 Pa reported in the literature. 36 In comparison, our HA hydrogels exhibited relatively low compressive moduli within a narrow range of 4.5-42.2 Pa. Others have found that a higher degree of modification for HA-ADH led to stiffer hydrogels, which was similar to what we observed for the 40 kDa hydrogels. 35 Ultimately, our method of fabricating hydrazone-crosslinked HA hydrogels yielded hydrogels with a wide range of physicochemical properties, including large ranges in hydrogel gelation time and mass change, with the capacity to swell, degrade, or maintain a relatively constant mass over 28 days depending on the molecular weight and concentrations of HA-ADH and HA-Ox used (Table 2).…”
Section: Hydrogel Mass Change Over Timesupporting
confidence: 85%
See 1 more Smart Citation
“…A wide range of compressive moduli have been observed with hydrazone-crosslinked HA hydrogels with values ranging between 1-2000 Pa reported in the literature. (36) In comparison, our HA hydrogels exhibited relatively low compressive moduli within a narrow range of 4.5-42.2 Pa. Others have found that a higher degree of modification for HA-ADH led to stiffer hydrogels, which was similar to what we observed for the 40 kDa hydrogels. (35) Ultimately, our method of fabricating hydrazone-crosslinked HA hydrogels yielded hydrogels with a wide range of physicochemical properties, including large ranges in hydrogel gelation time and mass change, with the capacity to swell, degrade, or maintain a relatively constant mass over 28 days depending on the molecular weight and concentrations of HA-ADH and HA-Ox used (Table 2).…”
Section: Hydrogel Mass Change Over Timesupporting
confidence: 85%
“…(30)(31)(32) We formed HA hydrogels using dynamic covalent hydrazone crosslinks as this approach can yield a wide range of physicochemical properties, making them an attractive hydrogel platform for numerous regenerative medicine applications. (33)(34)(35)(36)(37)(38)(39)(40) The properties of hydrazonecrosslinked HA hydrogels can be easily tuned by adjusting the ratios of the two dynamic covalent crosslinking polymers: oxidized HA (HA-Ox) and HA adipic acid dihydrazide (HA-ADH). Thus, we narrowed our input parameters to HA molecular weight, HA-Ox concentration, and HA-ADH concentration.…”
Section: Introductionmentioning
confidence: 99%